2018
DOI: 10.1002/1873-3468.13295
|View full text |Cite
|
Sign up to set email alerts
|

The PI 3‐kinase PI3KC2α regulates mouse platelet membrane structure and function independently of membrane lipid composition

Abstract: PI3KC2α is a phosphoinositide 3‐kinase with a recently reported function in platelets; PI3KC2α‐deficient mouse platelets have altered membrane structure and impaired function. Yet, how these membrane changes cause platelet dysfunction remains unknown. Here, focused ion beam‐scanning electron microscopy of PI3KC2α‐deficient platelet ultrastructure reveals a specific effect on the internal membrane structure, while liquid chromatography‐tandem mass spectrometry profiling of 294 lipid species shows unaltered lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Structural membrane alterations were also observed in PI3KC2α‐invalidated MKs. These defects in platelet ultrastructure are associated with abnormal membrane biophysical properties with a reduced elasticity, shown by atomic force microscopy, and defective dynamics, highlighted by a decreased tether and filopodia formation . This platelet membrane phenotype was not due to a modification of membrane lipid composition, as shown by sensitive lipidomic methods coupling liquid chromatography and mass spectrometry, or to an affected signaling downstream of major platelet receptors .…”
Section: Pi3kc2α‐dependent Ptdins3p Pool Is Essential For Membrane Momentioning
confidence: 98%
“…Structural membrane alterations were also observed in PI3KC2α‐invalidated MKs. These defects in platelet ultrastructure are associated with abnormal membrane biophysical properties with a reduced elasticity, shown by atomic force microscopy, and defective dynamics, highlighted by a decreased tether and filopodia formation . This platelet membrane phenotype was not due to a modification of membrane lipid composition, as shown by sensitive lipidomic methods coupling liquid chromatography and mass spectrometry, or to an affected signaling downstream of major platelet receptors .…”
Section: Pi3kc2α‐dependent Ptdins3p Pool Is Essential For Membrane Momentioning
confidence: 98%
“…Human and mouse platelets express PI3KC2α and β, but not PI3KC2γ [122]. Due to the lethality of PI3KC2α loss in mice, mouse studies have utilised heterozygous knock‐in of a kinase‐dead mutation (D1268A) at the endogenous locus [123], or inducible shRNA gene targeting [122, 124, 125]. PI3KC2α‐deficient mouse platelets show defective thrombus formation, forming accelerated but highly unstable thrombi under haemodynamic shear [122,123].…”
Section: Class II Pi3ks In Platelet Function and Thrombosismentioning
confidence: 99%
“…Loss of both PI3KC2α and PI3KC2β had no impact on agonist‐stimulated 3‐phosphoinositide levels, and confirmed that PI3KC2α's role in the regulation of platelet open canalicular structure and thrombus stability is non‐redundant, although VPS34 expression was increased in this context [125]. Subsequent work using ion beam‐scattering electron microscopy and mass spectrometry confirmed that the defect in platelet membrane structure observed for PI3KC2α‐deficient platelets is not associated with major changes in membrane lipid composition, but is due to increased OCS dilation, volume, and plasma membrane openings, with a potential impact on membrane tethering during thrombus formation [124]. It is important to note that a lack of selective inhibitors for the Class II PI3Ks has hampered further interrogation of their functional roles in many contexts, including whether the functional significance observed in mice will translate fully to humans.…”
Section: Class II Pi3ks In Platelet Function and Thrombosismentioning
confidence: 99%
“…Due to the lumen of the OCS having a diameter of around 20-30 nm in a resting platelet, they can only be observed through electron microscopy. In transmission electron microscopy images the OCS appears as irregularly-shaped, clear vacuoles occurring within the platelet interior, due to the inability of the extracellular fluid contained within the lumen to absorb or scatter electrons [5][6][7][8]. In contrast, the various platelet granules appear as electron dense structures of more regular size and shape.…”
Section: Ionps Into the Ocs Of Human Plateletsmentioning
confidence: 99%
“…However due to the complex geometry of the tunnel network, as well as its tiny lumen diameter (20-30 nm) [5], it has only been possible to study this structure by electron microscopy. This has led to the OCS being considered principally for its structural contributions to platelet activation, such as a site for granule fusion or as a membrane reservoir to allow shape change [6], membrane tether formation [7], or to facilitate platelet spreading over the subendothelial matrix [8]. Previously we showed that this structure may also play an important role in controlling platelet activation by acting as a dynamic Ca 2+ store that can be recycled back into the platelet cytosol through Ca 2+permeable ion channels [9].…”
Section: Introductionmentioning
confidence: 99%